Knowledge of and perception towards eclampsia among women and men in Unguja Island, Zanzibar: A qualitative study - Nassra Is-hak Yussuf; Jelle Stekelenburg; Michael Johnson Mahande; Rachel Nathaniel Manongi (PLoS ONE, 2025)
Background Eclampsia is among the primary causes of maternal and perinatal morbidity and mortality in Zanzibar. Many women and men are not aware of the signs, symptoms and causes of eclampsia and may have different explanatory models. Therefore, this study aimed to describe the community understanding of pre-eclampsia, as a key stage to improve maternal and perinatal health in Unguja Island, Zanzibar. Methods A qualitative study design of six focus group discussions (FDGs) was performed using a focus group interview guide; 51 male and female respondents at three selected wards of Unguja Island, Zanzibar participated. Thematic analysis was applied using Qualitative data analysis (QDA Miner Lite software version 2.0.9). Results Overall participants demonstrated a lack of understanding regarding eclampsia. The majority of participants perceived that there are certain things related to eclampsia: Mjusi or Mdudu (devil/satanic), superstitious issues, tension/stress from partners, food consumption, eating slaughtered meat like chicken, cow and goat during pregnancy, nice smelling lotion, soap and perfumes have been stated to be the causes of eclampsia. Spiritual and traditional remedies were mentioned as a treatment for eclampsia, including herbs, makombe (written verses of the Qur’an) and steaming (smoked dry leaves). Local names of eclampsia used by the communities, in urban and rural areas are mjusi (lizard) or mdudu (bug), which means the devil enters a woman’s body, especially during pregnancy or within 42 days post-delivery. Conclusion Most participants had a lack of understanding of eclampsia and perceived that there are traditional and spiritual issues related to its causes, attributed risks and clinical presentation, which makes them rely more on traditional and spiritual treatments. Therefore, health educational programs in the community setting and at the antenatal clinics, aiming at improving knowledge and dismissing myths and misperceptions regarding eclampsia, are recommended in rural and urban areas of Unguja Zanzibar.